Improvement of early miscarriage rates in women with adenomyosis via oxytocin receptor antagonist during frozen embryo transfer-a propensity score-matched study - Po-Wen Lin; Chyi-Uei Chern; Chia-Jung Li; Pei-Hsuan Lin; Kuan-Hao Tsui; Li-Te Lin (Reproductive Biology and Endocrinology, 2024)
Abstract Background Dysfunctional uterine peristalsis seems to play a pivotal role in hindering embryo implantation among women diagnosed with adenomyosis. This research aims to investigate whether administering an oxytocin receptor antagonist during a frozen embryo transfer (FET) cycle using a hormone replacement therapy (HRT) protocol can enhance in vitro fertilization (IVF) outcomes for infertile women affected by adenomyosis. Methods Between January 2018 and June 2022, our reproductive center conducted IVF-FET HRT cycles for infertile women diagnosed with adenomyosis. Propensity score matching was employed to select matched subjects between the two groups in a 1:1 ratio. Following this, 168 women received an oxytocin receptor antagonist during FET, constituting the study group, while the matched 168 women underwent FET without this antagonist, forming the control group. We conducted comparative analyses of baseline and cycle characteristics between the two groups, along with additional subgroup analyses. Results The study group exhibited notably lower rates of early miscarriage compared to the control group, although there were no significant differences in clinical pregnancy rates, ongoing pregnancy rates, and live birth rates between the two groups. Multivariate analysis revealed a negative correlation between the use of oxytocin receptor antagonists and early miscarriage rates in women with adenomyosis. Subgroup analyses, categorized by age, infertility types, and embryo transfer day, showed a substantial decrease in early miscarriage rates within specific subgroups: women aged ≥ 37 years, those with secondary infertility, and individuals undergoing day 3 embryo transfers in the study group compared to the control group. Furthermore, subgroup analysis based on adenomyosis types indicated significantly higher clinical pregnancy rates, ongoing pregnancy rates and live birth rates in the study group compared to the control group among women with diffuse adenomyosis. Conclusions Administering an oxytocin receptor antagonist during FET may reduce the early miscarriage rates in women with adenomyosis.